OPTIMALISASI EKSTENSIFIKASI DAN INTENSIFIKASI RETRIBUSI DAERAH PROVINSI BANTEN: ASET, TARIF, DAN LAYANAN PUBLIK - Sabferrial Fernando Imam (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2026)
Local revenue (PAD) serves as a critical fiscal instrument for achieving regional financial independence under Indonesia’s decentralized governance framework. Among its key components, local user charges (retribusi daerah) remain significantly underutilized, particularly in Banten Province, where their contribution to PAD averaged only 1.5%–2.2% between 2018 and 2022. This study aims to develop an integrated strategy to optimize regional user charges by simultaneously examining three interrelated dimensions: (1) asset-based extensification, (2) tariff rationalization through cost-recovery principles, and (3) service quality improvement via digital transformation. Employing a mixed-methods approach, this research combines descriptive quantitative analysis of fiscal records with thematic qualitative analysis from interviews and focus group discussions with 15 key stakeholders across local government institutions and service users. Results show that over 60% of regional assets remain unmapped or unmonetized, while tariff structures are outdated and often misaligned with the economic value of services. Moreover, fragmented institutional coordination and low service quality have hindered taxpayer compliance. The study proposes a policy framework emphasizing digital asset mapping, regular tariff benchmarking, integrated e-services, inter-agency coordination, and strategic human capital investment. By uniting asset management, pricing policies, and public service delivery into a cohesive model, this research offers both a theoretical contribution to fiscal decentralization literature and practical guidance for local governments seeking to enhance revenue performance. The novelty of this study lies in its multidimensional, evidence-based approach, bridging existing research gaps and supporting the formulation of context-responsive local fiscal policies.